The impact of ESG disclosure on corporate performance: Empirical evidence from Saudi Arabia's listed heavy-polluting companies - Hamdouni, Amina (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of environmental, social, and governance (ESG) performance on firm financial performance in the context of Saudi Arabia, focusing specifically on publicly listed companies operating in high-pollution industries during the period from 2010 to 2023. Using the Two-Step System Generalized Method of Moments (GMM) to address endogeneity and firm-specific effects, three financial performance measures return on assets (ROA), return on equity (ROE), and Tobin’s Q are analyzed. The results indicate a significant positive relationship between ESG performance and all three financial indicators, suggesting that strong ESG performance enhances firm value by improving stakeholder trust, market valuation, and operational efficiency. The study supports stakeholder theory, signaling theory, and the resource-based view within the ESG-performance context of emerging economies. While focused on Saudi Arabia, it provides a foundation for broader regional studies as ESG disclosure standards evolve in the Gulf. The findings highlight the importance of ESG practices for corporate managers, investors, and policymakers, especially under Saudi Arabia's Vision 2030. Policymakers may consider strengthening ESG disclosure to promote transparency and sustainable development, aligning corporate performance with national sustainability goals. This research contributes to the literature on ESG and firm performance in resource-intensive, emerging markets, underscoring the value of sustainable practices in high-pollution industries.